THE EFFECT OF WORK MOTIVATION, ORGANIZATIONAL COMMITMENT, PERSON ORGANIZATION FIT AND QUALITY OF WORK LIFE ON TEACHER PERFORMANCE IN BATAM CITY - Aufa’ Ulinnuha Safrizal; Herni Widiyah Nasrul; Moch Aminudin Hadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Teacher performance is the main basis for improving the quality of education and service in every education unit, especially in private schools. Therefore, teacher performance must be sustainably enhanced by studying the variables that influence it to determine related policies. This statement is believed to be an absolute truth because teachers are a core component that plays an important role in the implementation of effective education. This study aims to determine and analyze the influence of work motivation variables, organizational commitment, personal organization, and quality of work life on teacher performance in the context of private schools in Batam City. This research was conducted at Globe National Plus School, Batam City, using 200 permanent teachers as the sample for this study. To achieve the objectives of this study, quantitative research was applied, with statistical analysis using the Multiple Linear Regression method to analyze research data. The results of this study indicate that the independent variables, namely work motivation, organizational commitment, and person-organization fit, are empirically proven to have no significant effect on teacher performance in the context of private schools in Batam City. However, the variable quality of work life is proven to simultaneously affect teacher performance, work motivation, organizational commitment, person-organization fit, and quality of work life on teacher performance in the context of private schools in Batam City. The results of the study are very useful for the Batam City Education Office to review the policies set, as some independent variables in this study do not affect teacher performance. In addition, the government can also utilize the results of this new study as a policy formulation to optimize the improvement of the quality of teacher work life and improve teacher performance in the future.